Optimalisasi Potensi Gen Z Di Pedesaan Dalam Mengikuti Seleksi CPNS 2024 - Ibnu Phonna Nurdin; Dara Fatia; Annisah Putri; Uswatun Nisa; Saleh Sjafei; Riki Yulianda; Devi Intan Chadijah; Rachmat Tullah; Moh. Asri; Susvia Delta Kusdiane; Fasih Vidiastuti Sholihah (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
The narrowing of the workplace is one of the reasons for the high unemployment rate in Indonesia. This unemployment is also experienced by Generation Z, who are in the territory of Indonesia in general and the province of Aceh in particular. Therefore, it takes skills and skills for Generation Z to get a job. In addition to being an alternative job, being a civilian apparatus of the state also helps the government to realize the golden generation in 2045 because who will be the PNS at that time many are from Generation Z. There are 3 main activities given during this training: provision of choosing the right formation and instance, provisioning provisions for passing grade CPNS approval, and provision filling answers at the time of the CAT test. These three main activities are the core activities that are mandatory, followed by Generation Z as an initial step for implementing the CPNS test in 2024. The results of this dedication demonstrate that the participants understand the material given. The hope of this activity is that the participants can pass the CPNS test in 2024.